2019
DOI: 10.1186/s13104-019-4748-4
|View full text |Cite
|
Sign up to set email alerts
|

Liver enzyme elevation in patients taking HAART compared with treatment naïve controls at Debre Berhan Referral Hospital: a comparative cross-sectional study, Northeast Ethiopia

Abstract: ObjectiveHAART had significantly improved the quality of life of HIV patients. However, it results different adverse effects such as: hepatotoxicity, nephrotoxicity, lipodystrophy, anemia, diarrhea, psychiatric disorder and others. Therefore, this comparative cross sectional study was designed to investigate liver enzyme elevation in patients taking HAART compared with treatment naïve controls at Debre Berhan Referral Hospital.ResultA total of 152 individuals (76 cases and 76 controls) were included in this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 28 publications
(27 reference statements)
1
12
0
2
Order By: Relevance
“…The increase in the enzyme levels of HIV-treatment naïve patients (82) and those on HAART is welldocumented (52)(53)(54)(55). This study noted that the enzyme levels for a large proportion were just slightly above the normal limits; thus, suggesting that majority of the population were within mild to moderate enzyme elevations (54,57). In this study, more patients consumed alcohol than smoking or use of trado-medicine, with no sex-associated difference.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The increase in the enzyme levels of HIV-treatment naïve patients (82) and those on HAART is welldocumented (52)(53)(54)(55). This study noted that the enzyme levels for a large proportion were just slightly above the normal limits; thus, suggesting that majority of the population were within mild to moderate enzyme elevations (54,57). In this study, more patients consumed alcohol than smoking or use of trado-medicine, with no sex-associated difference.…”
Section: Discussionmentioning
confidence: 81%
“…On the other hand, patients who engage in anti-healthy social behaviors (36)(37)(38)(39) do have poorer outcomes in HIV management (43)(44)(45), and substance abuse is prevalent among people with HIV (67,68). Studies have documented, independently, that HAART (49)(50)(51)(52)(53)(54)(55) and certain social behaviors such as alcohol intake, smoking, and use of herbal remedies (40-42) have significant effects on the liver and may lead to mild to severe liver toxicity, and even death. The increase in the enzyme levels of HIV-treatment naïve patients (82) and those on HAART is welldocumented (52)(53)(54)(55).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed that PIs could increase the risk of dyslipidemia and myocardial infarction, with a relative rate of 1.13 for cumulative exposure of lopinavir-ritonavir per PY [18]. Patients receiving HAART have significantly higher liver enzyme level compared to treatment-naive HIV-infected patients [19]. All NNRTIs and PIs could cause liver cell damage, whereas the elevated liver transaminase levels would usually improve within 3 months [16,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Liver enzyme elevation is common among HIV-infected inpatients, and 50% of these patients are asymptomatic (5). The prevalence of mild and moderate liver enzyme elevations associated with steatosis/steatohepatitis among ART-treated patients was much higher than that among ART-naïve patients, mainly due to increased body mass index (BMI) (6)(7)(8). The liver damage incidence in China was highly observed within 6-12 months after ART initiation (9).…”
mentioning
confidence: 99%